DO SEED MOTHER’S SITES AFFECT THE QUALITY OF THE SEEDLINGS PRODUCED - Younis, Mohamed M.; Bugg, Younis Saeed Al; Hussein, Siham Thannon (International Journal of Research -GRANTHAALAYAH, 2020)
This experiment was conducted in (Zawita) area in Dohuk governorate / Iraq, and the morphological characteristics were studied by selecting four sites, four trees from each site, four sectors and, choosing twenty trees in each sector. Statistical analysis (RCBD) was done using the SPSS system. Through this study, it was found that Pinus brutia Ten. In Zawita, there is a clear effect on some morphological characteristics of the seedlings resulting from it. The first site was one of the best sites followed by the second site where he gave seedlings of good quality in terms of stem length with an average of 39.25 cm and the total weight of wet and dry seedlings with averages of 13.97 and 35.34 g respectively, and the third site was the lowest studied sites and gave seedlings of less quality than the rest of the sites where he scored Stem length averaged 23.06 cm while wet and dry weight was 7.68 and 22.17 g, respectively. As for the correlation between the variables, the relationship was positive and strong among all the variables except those between the length of the root and the rest of the variables except with the characteristic of the wet root weight. The highest correlation values were between total dry weight and total wet weight recording 0.960 and the lowest between the length of the root and the dry vegetative weight where the value was 0.070.